Stromal cyclin D1 promotes heterotypic immune signaling and breast cancer growth - Pestell, Timothy G. (Oncotarget, 2017)
The cyclin D1 gene encodes the regulatory subunit of a holoenzyme that drives cell autonomous cell cycle progression and proliferation. Herein we show cyclin D1 abundance is increased >30-fold in the stromal fibroblasts of patients with invasive breast cancer, associated with poor outcome. Cyclin D1 transformed hTERT human fibroblast to a cancer-associated fibroblast phenotype. Stromal fibroblast expression of cyclin D1 (cyclin D1(Stroma)) in vivo, enhanced breast epithelial cancer tumor growth, restrained apoptosis, and increased autophagy. Cyclin D1(Stroma) had profound effects on the breast tumor microenvironment increasing the recruitment of F4/80(+) and CD11b(+) macrophages and increasing angiogenesis. Cyclin D1(Stroma) induced secretion of factors that promoted expansion of stem cells (breast stem-like cells, embryonic stem cells and bone marrow derived stem cells). Cyclin D1(Stroma) resulted in increased secretion of proinflammatory cytokines (CCL2, CCL7, CCL11, CXCL1, CXCL5, CXCL9, CXCL12), CSF (CSF1, GM-CSF1) and osteopontin (OPN) (30-fold). OPN was induced by cyclin D1 in fibroblasts, breast epithelial cells and in the murine transgenic mammary gland and OPN was sufficient to induce stem cell expansion. These results demonstrate that cyclin D1(Stroma) drives tumor microenvironment heterocellular signaling, promoting several key hallmarks of cancer.